A Single Transcript Knockdown-Replacement Strategy Employing 5’ UTR Secondary Structures to Precisely Titrate Rescue Protein Translation - Millette, Matthew M.; Holland, Elizabeth D.; Tenpas, Tanner J.; Dent, Erik W. (Frontiers in Genome Editing, 2022)
One overarching goal of gene therapy is the replacement of faulty genes with functional ones. A significant hurdle is presented by the fact that under- or over-expression of a protein may cause disease as readily as coding mutations. There is a clear and present need for pipelines to translate experimentally validated gene therapy strategies to clinical application. To address this we developed a modular, single-transgene expression system for replacing target genes with physiologically expressed variants. In order to accomplish this, we first designed a range of 5’ UTR “attenuator” sequences which predictably diminish translation of the paired gene. These sequences provide wide general utility by allowing control over translation from high expression, ubiquitous promoters. Importantly, we demonstrate that this permits an entirely novel knockdown and rescue application by pairing microRNA-adapted shRNAs alongside their respective replacement gene on a single transcript. A noteworthy candidate for this corrective approach is the degenerative and uniformly fatal motor neuron disease ALS. A strong proportion of non-idiopathic ALS cases are caused by varied mutations to the SOD1 gene, and as clinical trials to treat ALS are being initiated, it is important to consider that loss-of-function mechanisms contribute to its pathology as strongly as any other factor. As a generalized approach to treat monogenic diseases caused by heterogeneous mutations, we demonstrate complete and predictable control over replacement of SOD1 in stable cell lines by varying the strength of attenuators.